Biosecurity the socio-politics of invasive species and infectious diseases - Dobson, Andrew; Barker, Kezia; Taylor, Sarah L. (Routledge, 2013)
Biosecurity is the assessment and management of potentially dangerous infectious diseases, quarantined pests, invasive (alien) species, living modified organisms, and biological weapons. It is a holistic concept of direct relevance to the sustainability of agriculture, food safety, and the protection of human populations (including bio-terrorism), the environment, and biodiversity. Biosecurity is a relatively new concept that has become increasingly prevalent in academic, policy and media circles, and needs a more comprehensive and inter-disciplinary approach to take into account mobility, globalisation and climate change. In this introductory volume, biosecurity is presented as a governance approach to a set of concerns that span the protection of indigenous biological organisms, agricultural systems and human health, from invasive pests and diseases. It describes the ways in which biosecurity is understood and theorized in different subject disciplines, including anthropology, political theory, ecology, geography and environmental management. It examines the different scientific and knowledge practices connected to biosecurity governance, including legal regimes, ecology, risk management and alternative knowledges. The geopolitics of biosecurity is considered in terms of health, biopolitics and trade governance at the global scale. Finally, biosecurity as an approach to actively secure the future is assessed in the context of future risk and uncertainties, such as globalization and climate change.